2021
DOI: 10.1007/s10903-021-01181-z
|View full text |Cite
|
Sign up to set email alerts
|

Parent Support Programmes for Families Who are Immigrants: A Scoping Review

Abstract: Parental support is of paramount importance in the promotion of positive parenting, strengthening parenthood and protecting children from disadvantages due to immigration experiences. The aim was to describe what is known about parent support programmes targeted to families who are immigrants. Electronic databases and the grey literature were systematically and comprehensively searched with no time/language restrictions. JBI approach and PRISMA-ScR were used to guide the review. N = 88 articles were sourced. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 110 publications
(555 reference statements)
1
17
0
Order By: Relevance
“…In the analysis stage of the ADDIE model, the participant and the environment surrounding the participant were thoroughly analyzed to deliver tailored health information to the target population. Looking at the existing parent support program for immigrants, it was found that most studies considered tailoring programs for cultural adaptation ( 31 ). However, by analyzing the participants and their surrounding environment, we found that there were difficulties in language, family conflicts, and application of information when parenting children.…”
Section: Discussionmentioning
confidence: 99%
“…In the analysis stage of the ADDIE model, the participant and the environment surrounding the participant were thoroughly analyzed to deliver tailored health information to the target population. Looking at the existing parent support program for immigrants, it was found that most studies considered tailoring programs for cultural adaptation ( 31 ). However, by analyzing the participants and their surrounding environment, we found that there were difficulties in language, family conflicts, and application of information when parenting children.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, forcibly displaced parents often experience exceptionally poor access to healthcare services, due to limited awareness of service availability, perceived stigma around mental health problems and fear of judgement, discrimination or child removal by service providers 18. Service access is further complicated for these families by the limited availability of culturally aligned services delivered in their native languages 19…”
Section: Introductionmentioning
confidence: 99%
“…Emerging research shows that parenting interventions that focus on improving the parent-child relationship may be a particularly promising approach for supporting forcibly displaced families ( Hamari et al, 2022 ). While some parenting programs that are culturally and contextually relevant to families exist, they are exceptionally scarce, despite the historically high rates of forcibly displaced people worldwide ( UNCHR, 2022 ).…”
Section: Introductionmentioning
confidence: 99%